Active videogames promotes cardiovascular benefits in young adults? Randomized controlled trial - Jorge L. de Brito-Gomes; Raphael J. Perrier-Melo; Aline de F. Brito; Manoel da C. Costa
Abstract Objectives To investigate how quickly active video games, structured and unstructured, provide changes in hemodynamic variables in young adults during a 6-week intervention. Method Twenty participants after baseline assessments, participants were randomized: structured active videogame (n = 6), unstructured active videogame (n = 7) and a control group (n = 7). Participants played their respective active videogame 3 times a week for 6-weeks (30 min-session). Results Structured active videogame in exactly 6 weeks shown improvements reducing the heart rate (heart rate; 14% of variation; p < 0.05). Otherwise, not confirmed to both active videogame interventions in systolic blood pressure but maintain the diastolic blood pressure during these 6 weeks (systolic blood pressure-unstructured: −2% and Structured: 11%; diastolic blood pressure-unstructured: 0% and structured: 0%; p > 0.05). Conclusions The 6-week training program with active videogame reduced the heart rate (structured - 6th week). However, active videogames generally do not promoted benefits for normotensive young adults.